Translation Techniques of Illocutionary Acts in Jack Canfield and Mark Victor Hansen Novel's "Chicken Soup for the Mother of Preschooler's Soul" - Amelia Novianti; A Soerjowardhana (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2020)
Abstract: This research entitled Translation Techniques of Illocutionary Acts in Jack Canfield and Mark Victor Hansen Novel's "Chicken Soup for the Mother of Preschooler's Soul". It is directed to find out the illocutionary acts and the translation techniques in translating quotes in target language. This research used descriptive-qualitative method.Based on the analysis, there are 3 illocutionary acts used including Representative occurs 65 times, represents 77,38%. Directive occurs 16 times, represents 19,05%. Commissive occurs 3 times, represents 3,57%. There are no Declaration and expressive illocutionary are found. The researcher also found there are 15 translation techniques by Molina Albir. They are Adaptation (4 data) 4,76%, Amplification (7 data) 8,33%, Pure Borrowing (1 data) 1,19%, Naturalized Borrowing (2 data) 2,38%, compensation (6 data) 7,14%, description (1 data) 1,19%, discursive creation (5 data) 5,95%, establish equivalent (9 data) 10,71%, generalization (1 data) 1,19%, linguistic amplification (15 data) 17,86%, linguistic compression (7 data) 8,33%, literal translation (12 data) 14,29%, modulation (2 data) 2,38%, particularization (3 data) 3,57%, reduction (4 data) 4,76%, transposition (5 data) 5.95%. The total data is 84. The technique of translation that the researcher found is dominated by Linguistic Amplification technique 17,86%. it is caused by illocutionary acts which contain mostly linguistic amplification that make the message more clearly to the target reader. From the findings, it concludes that the translator should know about the pragmatic, speech acts that involve illocutionary acts to maintain the intention from the author and understand the technique in translating text to get good translation to make the readers understand and get the message of the text.